Pengaruh Current Ratio, Firm Size, dan Net Profit Margin terhadap Cash Turn Over pada Perusahaan sektor Apparel & Luxury Goods yang Terdaftar di BEI - Evalia Safitri; Liza Zakiyah Nur Jannah (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of Current Ratio (CR), Firm Size, and Net Profit Margin (NPM) on Cash Turn Over (CTO) in Apparel & Luxury Goods sector companies listed on the Indonesia Stock Exchange (BEI) during the 2020-2024 period. Employing a quantitative approach and associative research type, the study utilizes secondary data from annual reports of 7 selected Apparel & Luxury Goods companies. The Random Effect Model was identified as the best model3. Classical assumption tests indicated normally distributed residuals (Prob > chi2 = 0.0904), no multicollinearity (VIFs < 10), and no autocorrelation (Prob > F = 0.0612). The F-test revealed that CR, Firm Size, and NPM simultaneously influence CTO (Prob > chi2 = 0.0000)7777. However, the t-test showed that NPM partially affects CTO (P > |t| = 0.000), while CR (P > |t| = 0.962) and Firm Size (P > |t| = 0.139) do not. The R-squared value of 0.3332 indicates that 33.32% of CTO variation is explained by the independent variables, with the remaining 66.68% influenced by other variables outside the model.